Implementation of Green Economy in Increasing Economic Growth and Environmental Conservation - Moh Afrizal Miradji; Rina Fariana (SEAN Institute, 2024)
The green economy is a sustainable economic model that fosters growth while ensuring the preservation of natural resources. This paper explores the role of green economy practices in promoting both economic growth and environmental conservation. It examines the integration of green technologies, renewable energy, and sustainable agriculture into various sectors, highlighting their impact on job creation, environmental benefits, and long-term economic stability. By analyzing case studies and policy frameworks, this paper demonstrates that the green economy can be a driving force for achieving both economic prosperity and environmental sustainability.